Postcard, 1928 Christmas Services and Annual Parish Dinner - Patrick, William E.; St. Paul's Episcopal Church (Bakersfield, Calif.)
Postcard announcing 1928 Christmas and Advent services at St. Paul's Episcopal Church, and Annual Parish Dinner. Heading reads, "Christians, Awake, Salute the Happy Morn!"